Produção e purificação de enzimas amilolíticas para hidrólise enzimática de biomassa de Spirulina - Rodrigues, Ellen Francine (2016)
Production and use of microbial enzymes is one of the main sectors of biotechnology industry. It has presented applications in several industrial sectors and the most recent ones are the processes of biomass enzymatic hydrolysis for producing bioethanol. The production of third-generation, microalgae-derived, bioethanol has been an alternative proposal, but the costs of its production have not enabled its application in a larger scale yet. One of the production bottlenecks of third-generation bioethanol is the need for obtaining enzymes to apply in microalgae biomass. We aimed at producing and purifying amilolitic enzymes and their application in intracellular hydrolysis of polysaccharides of Spirulina microalgae. The production of enzymes was performed by using solid submerged bioprocesses, being the wheat bran its main component for cultivation. The enzymatic extracts obtained through bioprocesses were purified with ammonium sulfate precipitation and/or microfiltration and evaluated regarding its thermal stability. The purified enzymes were immobilized through process of encapsulation in polyurethane support. Spirulina platensis LEB 52 microalgae was cultivated in conditions previously studied for accumulation of intracellular carbohydrates and the dry biomass was used to studying the process of enzyme hydrolysis. Before, we studied a pre-treatment for biomass using Spirulina sp. LEB 18, which contained normal contents of carbohydrates and commercial enzymes. The variables of the study were: thermal treatment, ultrasound and microwaves. Later, we performed the process of cultivated microalgae Spirulina platensis LEB 52) biomass hydrolysis: using free or immobilized purified enzymes produced in this study. The response variable of the hydrolysis process was the amount of reducing sugars generated. It was possible to obtain amilolitic activities after bioprocesses in both cultivation ways. We obtained 24.63 U/g fermentedbran from solid state fermentation and 0.79 U/mL in submerged fermentation. After microfiltration, specific activities were obtained in the retained fraction being 103.06±0.71 U/mgprotein during submerged fermentation and 50.77±0.19 U/mg protein in solid state fermentation. The microfiltered enzymatic extracts were stable at 40 °C and in between 50 ºC - 60 ºC during 24 h, respectively for solid state and submerged fermentation. The immobilization of purified enzymes in polyurethane presented outputs of 332 % and 205 % respectively for submerged and solid state fermentation. The selected pre-treatment was the thermal treatment at 121 ºC, 101 kPa, for 30 min. In the process of enzyme hydrolysis, using the enzyme produced in the fermentation processes, the amount of reducing sugars generated has increased during the process, both for microfiltered free and immobilized enzymes. It can be concluded that there was production of enzymes in both fermentation processes studied and that they can be applied to biotechnological processes. The results obtained in the process of enzyme hydrolysis have shown that both free and immobilized enzymes favored generation of fermentable sugars. The use of amilolitic enzymes on microalgae polysaccharides hydrolysis is considered a promising alternative for developing the concept of bio-refineries using microalgae biomasses.